Home energy monitoring system towards smart control of energy consumption - Jebroni, Zakariae (2019)
The need to manage, control and reduce energy consumption has led researchers to propose reliable solutions based on new technologies to achieve this goal. Our contribution in this subject is presented in this paper and consists of the design, implementation and testing of a home energy monitoring system. The presented system is dedicated for residential customers and allows the monitoring and control of the energy consumption, based on distributed and central processing. The system includes distributed monitoring devices, a gateway and a graphical user interface (GUI). To connect the all parts we use a hybrid wireless solution based on the Wi-Fi and Bluetooth Low Energy standards. We present the design and the implementation of the monitoring device hardware as well as the embedded software used to calculate the electrical quantities. We also present the calibration methodology used to eliminate gain and offset errors. In terms of performance test results, we have achieved voltage measurement accuracy below 0.2% and current measurement accuracy below 0.5%. A GUI was also developed for the user to visualize and control remotely the household appliances.